Effect of mycorrhizal fungi inoculation on growth of mahaleb cherry (Cerasus mahaleb (L.) Mill.) seedlings in greenhouse condition - Negin Armand; Mohammad Matinizadeh; Anooshiravan Shirvany; Mostafa Khoshnevis (تحقیقات جنگل و صنوبر ایران, 2016)
Arbuscular mycorrhizal fungi (AMF) are soil microorganisms that play an important role in ecosystem processes. They are able to increase the water uptake and mineral nutrients to the plant roots, and thus improve establishment, growth and survival of plants. Here, the effect of mycorrhizal fungi (Glomus intraradices, G. mosseae and G. hoi) on growth parameters of seedlings of mahaleb cherry (Cerasus mahaleb (L.) Mill.) under greenhouse condition were investigated.. To produce the Cerasus mahaleb seedlings, seeds of native trees were collected in Chahar Tagh- Ardal, Chaharmahall and Bakhtiari province. After one growth season, mycorrhizal and control seedlings were evaluated. Results of measurements on root colonization showed that fungal can establish well symbiosis with Cerasus mahaleb seedlings.. The results also revealed that mycorrhizal fungi significantly influenced all parameters except the length of main root and plant development, while G. hoi did not significantly affect the growth parameters and established a weakk symbiosis. Overall, using of G. intraradices and G. mosseae were assessed to be positive here, therefore it can bee applied as an appropriate way to increase the seedling growth and establishment in Cerasus mahaleb, particularly in the degraded areas of Zagros forests.